Goal Setting in Family Firms: Goal Diversity, Social Interactions, and Collective Commitment to Family–Centered Goals - Kotlar, Josip; De Massis, Alfredo (Entrepreneurship Theory and Practice, 2013)
Goal setting in family firms is very complex due to the interplay between family and business systems. However, this topic is largely overlooked in family business research. In this qualitative study of goals and goal formulation processes among 76 organizational members across 19 family firms, we identify goal diversity as a direct consequence of the overlap between the family, ownership, and business systems. We found that goal diversity is expressed more strongly in the proximity of generational transitions, triggering social interaction processes through which organizational members contrast their goals. Our findings suggest that different types of social interactions lead to different behaviors, with familial social interactions being more effective than professional social interactions in managing goal diversity toward the formation of collective commitment to family–centered goals.